Theravada Literature After “Roads Taken and Not Taken”: Reflections on Recent Textual Studies - Walker, Trent (Journal of global buddhism, 2021)
This article sketches the study of Theravada Buddhist literature over the past twenty-five years. Drawing on Charles Hallisey’s influential essay, “Roads Taken and Not Taken in the Study of Theravāda Buddhism,” I survey the ways in which scholars have heeded his calls to study texts beyond the canon, to attend to issues of translation, and to examine the local production of meaning. I show how these calls correspond to three recent trends: increased emphasis on non-canonical Pali and vernacular texts; a renewed interest in multilingual texts and the cultures of translation that shaped them; and new models for charting intellectual histories of Theravada Buddhist societies beyond local confines.